2017
DOI: 10.1016/j.ejrad.2017.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Prospective intra-individual comparison of standard dose versus reduced-dose thoracic CT using hybrid and pure iterative reconstruction in a follow-up cohort of pulmonary nodules—Effect of detectability of pulmonary nodules with lowering dose based on nodule size, type and body mass index

Abstract: Diagnostic performance of lung nodule is affected by nodule size, protocol, reconstruction algorithm and patient's body habitus. The protocol in this study showed that RD1 was superior to RD2 for assessment of solid nodules ≤4mm, and subsolid nodules ≤5mm and deterioration of RD2 is related to patient's body mass index.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 28 publications
(31 reference statements)
2
9
0
Order By: Relevance
“…[ 16 18 ] For this reason, van Klaveren et al [ 15 ] defined growth on serial CT scans as an increase in measured volume of over 25%. Limits of agreement observed in our study are within this measure, and consistent with, or tighter than [ 21 23 ] prior limited reports regarding observed differences between LDCT and ULDCT imaging. As nodule size decreased, we observed more outliers, which is most likely due to measurement variability which differentially affects smaller nodules.…”
Section: Discussionsupporting
confidence: 92%
“…[ 16 18 ] For this reason, van Klaveren et al [ 15 ] defined growth on serial CT scans as an increase in measured volume of over 25%. Limits of agreement observed in our study are within this measure, and consistent with, or tighter than [ 21 23 ] prior limited reports regarding observed differences between LDCT and ULDCT imaging. As nodule size decreased, we observed more outliers, which is most likely due to measurement variability which differentially affects smaller nodules.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies on ULD CT also excluded participants with obesity (28,29). Vardhanabhuti et al (30) found that the detectability of pulmonary nodules was reduced in individuals with higher BMIs due to higher image noise, and they concluded that ULD CT may not be suitable for overweight people. In our study, seven of 226 candidates had a BMI higher than 30 kg/m 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Peer reviewed literature characterization: Quantitative measurements are improved and the noise power spectrum shifts towards lower frequencies compared to both filtered back projection and ASiR (37,(56)(57)(58). Hounsfield units are shifted to lower values at low doses (59).…”
Section: Veomentioning
confidence: 99%